The success rate and complications of awake caudal epidural bupivacaine alone or in combination with intravenous midazolam and ketamine in pre-term infants - Mahin Seyedhejazi; Majed Mashhoori; Rasoul Azarfarin; Daryoush Shekhzadeh; Nasrin Taghizadieh (Wolters Kluwer Medknow Publications, 2015)
Background: The aim of the present study is to compare the success rate and complications of caudal epidural bupivacaine alone or in combination with intravenous (IV) midazolam and ketamine in awake infants undergoing lower abdominal surgery. Materials and Methods: In this double-blind, clinical trial study, 90 infants (aged below 3 months and weight below 5 kg) with American Society of Anaesthesiologists I-II, were divided into three groups of each 30: Group 1 received bupivacaine 0.25%, 1 mL/kg for caudal epidural block; Groups 2 and 3 received caudal block with same dose bupivacaine along with IV pre-treatment with midazolam 0.1 mg/kg or IV midazolam 0.1 mg/kg and ketamine 0.3 mg/kg, respectively. Results: The success rates in Groups 2 and 3 were 93.3% and 93.1%, respectively, compared with a caudal block with bupivacaine alone 80%; P = 0.015). There was no significant difference among the three groups in terms of mean systolic and diastolic blood pressures and mean heart rate at intervals of 0, 20, 40 and 60 min (P < 0.05). There were no significant differences in the pain scores >3 on the Neonatal Infant Pain Scale at three intervals (30, 60 and 120 min) after surgery among the three groups. The complications such as apnoea or desaturation were not found in any of the studied groups. Conclusions: Adding IV ketamine and/or midazolam to bupivacaine caudal epidural block in the conscious infants can positively affect block success rate.